O deontologii metodologii filozofii - Stanisław Jakóbczyk (Przestrzenie Teorii)
A nomothetic character of philological researches, suggested by the quoted authors, requires - if we stay for satisfying at last some main methodological criteria of scientific validity - a publication, a diffusion of texts which are supposed to inform about these researches. They are metatexts from nature of things, the very "texts" being their subjects. However, these subject-texts are included, also as quotations, and thus, they are also published and diffused. The logical and deontological problem is, that among them may (and even must) appear some morally reprehensible texts. The latter, in their nature, become such (or increase their negative character) precisely as a result of publication and diffusion. Does a philologist act in reprehensible manner?